dasar pendidikan islam Dasar-dasar pendidikan islam dalam perspektif filsafat pendidikan islam - Alif Nazarsyah; Mustofa Ismail; Prayoga Sukma; M Fadil Luthfi Lubis (Jurnal Pendidikan Islam, 2025)
The teaching method in Islam should be adopted comprehensively, especially based on the philosophy of Islamic education. This study attempts to uncover the basics of Islamic education in the philosophy of islamic education, especially through ontology, epistemology, and axiology. This study was conducted using a qualitative descriptive method through a literature review. The result is that the most iterative basis of Islamic education is the existence of a comprehensive view of humans and its purpose is specifically to form a perfect human being. The most important contribution resulting from this study is to systematically combine the three dimensions of philosophy in the study of the integration of Islamic education. With the condition that there is an effort to strengthen the logic in the curriculum and practice of contemporary Islamic education. This can only be done if the dynamic Islamic education remains subject to the changes that occur in the world.